Activities of Āgenskalns Gymnastics and Sports Society and Its Headquarters at 7 Baldones Street - Apine, Rita (History of Engineering Sciences and Institutions of Higher Education, 2021)
Āgenskalns Gymnastics and Sports Society was one of the largest and best-known Baltic-German sports organizations in the first half of the 20th century. Sports enthusiasts of various professions, including engineers, participated in the activities of this society. The house built by the Society in 1910 at 7 Baldones S treet, Riga, which has been rebuilt several times, played an important role in the sports life. The research presents comprehensive documentary evidence about the Society until the repatriation of the Baltic- Germans in 1939 and the history of its headquarters building. Using the documents and press materials from the Latvian State Historical Archive (LSHA) of the National Archives of Latvia (NAL), archive documents of the Riga Construction Board, as well as the collection of the Latvian Sports Museum, previously unknown facts have been revealed.